GENERATION OF MULTITEMPORAL THERMAL ORTHOPHOTOS FROM UAV DATA - K. Pech; N. Stelling; P. Karrasch; H.-G. Maas (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2013)
The paper deals with using a TIR camera on an UAV for acquiring multitemporal thermal images of a building block against the background of detecting, monitoring and analysing urban heat islands. It is motivated by a research project called EO2HEAVEN (Earth Observation and Environmental Modelling for the Mitigation of Health Risks) which analyses the influence of environmental effects to human health. Therefore, the aim is the generation of thermal orthophotos from UAV data which can be used for further thematic analysis. The paper describes the data acquisition on the one hand and the processing of the obtained data on the other hand. The data acquisition comprises three image flights at different times of day from which only the first two missions could be processed until now. The low image contrasts, the radiometric differences between images as well as the poor initial positioning and orientation values limit the suitability of available software for automatic tie point measurement so that this step was outsourced and implemented in C++. The following aerial triangulation and orthophoto generation was realised in TerraPhoto (Terrasolid). However, two orthophotos could be generated with a geometric resolution of 15 cm. Furthermore, the radiation temperatures from the thermal images were compared to ground measurements to check the correctness of the camera measurements.